Early-life homeostatic differentiation of thymus-resident B cells into memory B cells - Castañeda, Justine; Poblete, Lilian; Rosemblatt, Mariana V.; Sauma, Daniela; Rosemblatt, Mario; Bono, María Rosa; Nuñez, Sarah (Frontiers in Immunology, 2025)
The thymus contains various antigen-presenting cells, including B cells, which remain activated even under steady-state conditions, suggesting ongoing local stimulation. In this study, we identify class-switched memory B cells in the thymus. Some of these cells switch their immunoglobulin to IgG2b and IgA, and express typical memory markers CD73 and PD-L2. Memory B cell differentiation in the thymus begins in neonatal mice, preceding the appearance of class-switched B cells in other peripheral lymphoid organs. Notably, exposure to environmental antigens does not influence their differentiation. Additionally, cognate interaction with CD4+ positive thymocytes is crucial for the development of memory B cells in the thymus. Our findings demonstrate that the thymus supports the local differentiation of memory B cells through a steady-state process, independent of foreign antigen stimulation and driven by interactions with developing T cells.